Modelagem matemática como enfoque para o ensino - Araújo, Gilberto Faria de (2017)
One of the main objectives of this work is to articulate theoretical and methodological aspects that support the use of mathematical modeling as a mediator tool in solving problem situations in the teaching and learning process of Mathematics.For this purpose, a qualitative bibliographical approach is focused, along with others, in the conceptions and conceptualizations of the modeling according to some researchers of this theme, outlining subsidies for its implementation in educational activities. As results of this process, mathematical modeling is presented according to a brief historical context, sequenced by its insertion into teaching, its perspectives, its conceptualizations and possible steps for its application, its challenges and contributions, as well as some applications.